2019
DOI: 10.3390/molecules24224113
|View full text |Cite
|
Sign up to set email alerts
|

Reflectometry Reveals Accumulation of Surfactant Impurities at Bare Oil/Water Interfaces

Abstract: Bare interfaces between water and hydrophobic media like air or oil are of fundamental scientific interest and of great relevance for numerous applications. A number of observations involving water/hydrophobic interfaces have, however, eluded a consensus mechanistic interpretation so far. Recent theoretical studies ascribe these phenomena to an interfacial accumulation of charged surfactant impurities in water. In the present work, we show that identifying surfactant accumulation with X-ray reflectometry (XRR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 80 publications
(142 reference statements)
1
17
0
Order By: Relevance
“…Comparable films have been reported in other NR studies at interfaces with high and low interfacial energies, which are postulated to arise from fluid density depletion and/or gas present at the interface 35 38 . It has also been suggested that impurities within solvents and solutes could form similar layers at solid–liquid interfaces 39 , 40 . Possible contaminants at the iron oxide–dodecane interface are suggested to be gaseous molecules introduced from the atmosphere or polar contaminants that are native within the solvent, such as ambient dissolved water.…”
Section: Resultsmentioning
confidence: 99%
“…Comparable films have been reported in other NR studies at interfaces with high and low interfacial energies, which are postulated to arise from fluid density depletion and/or gas present at the interface 35 38 . It has also been suggested that impurities within solvents and solutes could form similar layers at solid–liquid interfaces 39 , 40 . Possible contaminants at the iron oxide–dodecane interface are suggested to be gaseous molecules introduced from the atmosphere or polar contaminants that are native within the solvent, such as ambient dissolved water.…”
Section: Resultsmentioning
confidence: 99%
“…The center frequency of their IR pulses was higher (∼2800 cm –1 ) and they used a continuous D 2 O phase, so the lack of free OD could be due to IR absorption by the D 2 O aqueous phase. However, recent neutron and X-ray reflectivity experiments have identified that trace impurities occupy the “bare” alkane–water interface …”
Section: Resultsmentioning
confidence: 99%
“…This charge accumulation has not just been observed on the nanoemulsion surface, but has also been measured at the air–water, solid–water, and self-assembled monolayer–water interfaces. , Despite the ubiquitous nature of charge accumulation at aqueous–hydrophobic interfaces, there is no broad consensus on the identity of the charge carrier. Mainstream theories on the origins, illustrated in Figure , of the droplet’s charge include the interfacial adsorption of negatively charged ions, ,, charge transfer mechanisms originating from asymmetric interfacial hydrogen-bonding environments, , and surface-adsorbed impurities. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations